Bis(9-aminoacridinium) bis(pyridine-2,6-dicarboxylato-κ(3) O (2),N,O (6))manganate(II) trihydrate - Eshtiagh-Hosseini, Hossien (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, (C(13)H(11)N(2))(2)[Mn(C(7)H(3)NO(4))(2)]·3H(2)O, consists of a discrete mononuclear [Mn(2,6-pydc)(2)](2−) anionic complex (2,6-pydc is pyridine-2,6-dicarboxylate) associated with two 9-aminoacridinium counter-ions for neutralization of charge and three uncoordinated water molecules. The Mn(II) atom is six-coordinated by (2,6-pydc)(2−) anions in a tridentate fashion and is at the centre of a distorted octahedron formed by the MnO(4)N(2) bonding set. In the crystal, various intermolecular interactions between different moieties can be found, such as different kinds of hydrogen bonds, offset or slipped π–π [centroid–centroid distances in the range 3.3704 (12) to 3.8674 (13)Å] and C=O⋯π [3.563 Å] interactions, which lead to the formation of a three-dimensional supramolecular network.